Analysis of a Numerical and Adaptive Control Servomechanism - Elbestawi, Abdel Aziz Mohamed (My University, 1976)
The purpose of this project was to analyze the Numerical and Adaptive Control system of a CNC milling machine, in order to improve the time response of the system while maintaining its stability. The available linear control theory as well as the state space method were used to study and simulate the behaviour of the N/C loop. The N/C system was tested to determine the practically optimum values of position and velocity gains. The Adaptive Control system consists of a cutting force transducer, and an Analog to Digital Processor which supply input to an A/C routine resident in the HP-2100A minicomputer. Both classical control theory and the state space technique were also used to investigate the operation of the A/C loop and to predict the response of the actual system.
Keywords: Mechanical Engineering; Mechanical Engineering